Challenges and Strategic Opportunities for the Competitiveness of the Hungarian Food Economy - Rajczi, Alexandra (Acta Scientiarum Socialium, 2015)
Challenges and Strategic Opportunities for the Competitiveness of the Hungarian Food Economy. Hungary’s food economy as an export-oriented branch improving trade balance went through significant changes during the previous decades. It had to face new challenges, such as a new ownership structure, the expectations of the society and an increasing number of products on the market. Hungary has favourable conditions to create a competitive and developed agribusiness. It is expected socially as well as economically and also a common target to use the national resources in the most optimal way in order to increase GDP and employment in accordance with CAP directives and the conditions of the global economy. However, the Hungarian agriculture is characterised by structural tensions and its competitiveness is also below expectations. It does not exploit its natural and human resources sufficiently and optimally. The significance of food economy is more and more salient as a result of the rocketing global demand for food and the regional and ecological barriers of food production. For countries with comparative advantages, such as Hungary, it should be a major goal to use this advantage as optimally as possible. It is the fundamental interest of the national economy that food economy – by regaining and strengthening its previous competitiveness - can contribute to meeting domestic food requirements and to promoting the development of the whole economy.